Client's Experiences of Online Counseling: Satisfaction and Therapeutic Alliance - Zeren, Serife Gonca; Erus, Seher Merve; Amanvermez, Yagmur; Genc, Arzu B. U. Y. R. U. K.; Duy, Baki (CUKUROVA UNIV, 2022)
Online counseling has been increasingly becoming widespread. Nevertheless, the number of studies investigating counselees' online counseling experience in-depth is scarce, especially in Turkey, despite the proliferation of the service. Therefore, this phenomenological study aims to understand the experiences of participants who received online counseling regarding satisfaction and therapeutic alliance. For this purpose, semi-structured interviews were conducted with six participants. Thematic analysis was applied to explore their satisfaction with online counseling and therapeutic alliance. The results showed that three themes emerged for satisfaction with online counseling; improvements in the symptoms, the flexibility of the online counseling, and limitations of online counseling. Thematic analysis of therapeutic alliance revealed the themes; goals, tasks, and bond. As a result, the participants reported high satisfaction with the online sessions, and they were able to establish a therapeutic alliance with their counselor in setting goals, seeking solutions to problems, and bonding. Overall, most of the participants reported positive experiences with online counseling in terms of improvement in their situation and establishing significant relationships with their counselor over the Internet.
Keywords: Online counseling; Face-to-face counseling; Clients' satisfaction; Therapeutic alliance; FACE-TO-FACE; VIDEOCONFERENCING PSYCHOTHERAPY; WORKING ALLIANCE; INTERNET; INTERVENTION; PERSPECTIVES; DEPRESSION; ATTITUDES; SERVICES; Education & Educational Research